2016
DOI: 10.1007/s11011-016-9873-3
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic treatment with acai frozen pulp prevents the brain oxidative damage in rats with acute liver failure

Abstract: Acai has been used by the population due to its high nutritional value and its benefits to health, such as its antioxidant properties. The aim of this study was to evaluate the protective effect of acai frozen pulp on oxidative stress parameters in cerebral cortex, hippocampus and cerebellum of Wistar rats treated with carbon tetrachloride (CCl). Thirty male Wistar rats (90-day-old) were orally treated with water or acai frozen pulp for 14 days (7 μL/g). On the 15th day, half of the animals received treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Xie and colleagues evaluated flavonoids isolated from açaí pulp and observed a reduction in serum levels, gene expression and protein levels of both the cytokines TNF-α and IL-6 in the resident macrophages cells [ 73 ]. Açaí was also able to prevent increases in the levels of IL-1β and TNF-α in the brain tissues of a CCI4 experimental model [ 27 ]. In addition, açaí reduced the COX-2 expression and PGE 2 levels in an experimental model of endometriosis [ 55 ] and reduced the MPO levels in a rat renal ischemia/reperfusion model [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie and colleagues evaluated flavonoids isolated from açaí pulp and observed a reduction in serum levels, gene expression and protein levels of both the cytokines TNF-α and IL-6 in the resident macrophages cells [ 73 ]. Açaí was also able to prevent increases in the levels of IL-1β and TNF-α in the brain tissues of a CCI4 experimental model [ 27 ]. In addition, açaí reduced the COX-2 expression and PGE 2 levels in an experimental model of endometriosis [ 55 ] and reduced the MPO levels in a rat renal ischemia/reperfusion model [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poulose et al (68) showed that an acai berry rich diet could modulate oxidative stress and enhance endogenous antioxidant enzyme defence through decreased prooxidant NADPH-oxidoreductase-2 (NOX2) and increased expression of nuclear factor erythroid 2-related factor 2 (Nrf2) in the hippocampus and frontal cortex of elder rat brains. A study on a hepatic encephalopathy animal model with neurological symptoms illustrated that 14 days of acai berry treatment prevented creatine kinase (CK) activity inhibition, antioxidant enzyme catalase (CAT) activity reduction, oxidative damage involving increasing levels of lipid peroxidation and protein carbonyl groups in the cerebral cortex, hippocampus, and cerebellum (69). Moreover, the frozen pulp was able to restore the decrease in superoxide dismutase (SOD) activity in the hippocampus (69).…”
Section: Euterpe Precatoria (Ep) Andmentioning
confidence: 99%
“…Among other studies, acai showed antiparasitic activity against L. infantum and L. amazonensis without cytotoxic effects to the host cell [18], reduction of early carcinogenesis in the colon of mice, mitigation of DNA damage induced by azoxymethane [19], antitumorigenic potential in the MCF-7 cell line [20], reduction in selected markers of metabolic disease risk in overweight adults [21], protection against renal damage in diabetic rats [22], inhibition of urinary bladder carcinogenesis in mice [23], improvement of cardiac dysfunction and exercise intolerance in rats subjected to myocardial infarction [24], and prevention of oxidative damage in the brain of rats [25].…”
Section: Monographsmentioning
confidence: 99%